Pengaruh Model Cooperative Tipe Two Stay Two Stray Terhadap Hasil Belajar IPS Murid Kelas IV SDN 113 Inpres Barugae Kecamatan Camba Kabupaten Maros - Ulul Azmi Ramadani; Syarifah Aeni Rahman; Rubianto Rubianto (Departement of Mathematics Education, 2024)
The influence of the Two Stay Two Stray Cooperative Learning Model on the social studies learning outcomes of Class IV students at SDN 113 Inpres Barugae, Camba District, Maros Regency. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Syarifah Aeni Rahman, and supervisor II Rubianto. This research is a type of experimental research. This research uses a one-group pretest-posttest design. Where in this study a sampling technique was used, namely saturated sampling, where the entire population in this study was sampled as 19 students. This research aims to determine the effect of the Two Stay Two Stray Cooperative learning model on the social studies learning outcomes of Class IV students at SDN 113 inpres Barugae, Camba District, Maros Regency and to determine student learning outcomes before and after using the Two stay two stray type cooperative learning model on the results. studying social studies for Class IV students at SDN 113 inpres Barugae, Camba District, Maros Regency. Data collection techniques use tests, observation sheets and documentation. The research instrument used observation sheets and learning outcomes tests. The results of the research in class IV of SDN 113 Inpres Barugae showed that the average value of the post-test learning results was greater than the average value of the pretest learning results or 88.24% > 61.83%. And also the number of students who completed the pretest was less than the posttest learning results. Where the number of students who completed the pretest was 6 students with a percentage of 31.58%. less than during the posttest with 16 students completing the test with a percentage of 84.21%.